THE EFFECT OF CURRENT RATIO AND SIZE FIRM ON RETURN SAHAM FOOD AND BEVERAGE - Kristian Chandra (Universitas Trisakti, 2017)
The objective of the research is to analyze the influence of current ratio and size firm to stock return. In this study the subjects taken were stocks that entered the food and beverage sector that were listed on the Indonesia Stock Exchange (IDX) during 2010 - 2015. The selection of samples in this study was conducted by Purposive Sampling in order to obtain a representative sample according to predetermined criteria. The number of food and beverage industry samples that meet the criteria are 13 listed on the Indonesia Stock Exchange in 2010-2015. The data analysis technique used regression analysis with the help of the EViews program. The results confirm that the current ratio has a positive but not significant effect on stock returns and the size firm has a negative and significant effect on the return of food and beverage stocks listed on the IDX in 2010-2015.